Juridical Review of the Auction of Collateral Items Due to Default - Liauw, Jonathan; Wijaya, Jonathan Kenneth; Lingga, Elya Fransisco Beckham; Martinelli, Imelda (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Based on the research results, it can be concluded that collateral objects that are not bound by mortgage rights can basically still be used as collateral in a loan agreement or credit guarantee. However, in practice, if there is a default, the execution of the collateral object is difficult because it has to go through litigation or a court suit which takes a long process and harms the creditor in the end. So that the collateral object should be tied to the guarantee institution to provide strong executorial confiscation powers. Likewise with acts of default committed in this case carried out by creditors who are late in fulfilling their obligations to pay debts as agreed. However, in this case the District Court which decided the case exceeded the limits of its authority.